2020
DOI: 10.1029/2020ja027844
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of O/N2 on Different Pressure Levels From GUVI Limb Measurements

Abstract: The ratio of O number density to N2 number density (O/N2) is an important parameter to describe thermospheric composition changes and its effects on the ionosphere. Based on Global Ultraviolet Imager (GUVI) limb measurements, we investigate the seasonal behaviors of O/N2 volume density ratio on different constant pressure levels during geomagnetically quiet periods. The global O/N2 shows the prominent annual and semiannual variations with solar activity dependence. An empirical model considering the solar acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 68 publications
(90 reference statements)
1
17
0
Order By: Relevance
“…( 2019 ) and Yu et al. ( 2020 ) found that the annual and semiannual variations in composition have a constant phase with altitude throughout the thermosphere. Figure 7a shows GOLD 3‐year average ∑ O/N 2 (2019, 2020, and 2021) for 42.5°N and 22.5°N from Figure 6 of this paper, and GUVI 3‐year average O/N 2 (2004, 2005, and 2006) at 8.4 × 10 −4 Pa (∼130 km) in the latitude bins of 50°N–30°N and 30°N–10°N based on Figure 6 of Yue et al.…”
Section: Discussionmentioning
confidence: 97%
“…( 2019 ) and Yu et al. ( 2020 ) found that the annual and semiannual variations in composition have a constant phase with altitude throughout the thermosphere. Figure 7a shows GOLD 3‐year average ∑ O/N 2 (2019, 2020, and 2021) for 42.5°N and 22.5°N from Figure 6 of this paper, and GUVI 3‐year average O/N 2 (2004, 2005, and 2006) at 8.4 × 10 −4 Pa (∼130 km) in the latitude bins of 50°N–30°N and 30°N–10°N based on Figure 6 of Yue et al.…”
Section: Discussionmentioning
confidence: 97%
“…∑O/N 2 is obtained by integrating densities of O and N 2 from infinity down to an altitude where the column number density of N 2 is 1 × 10 17 /cm 2 and thus it is actually defined on a constant pressure surface with no altitude information (Correira et al., 2020). O and N 2 number densities decrease exponentially with altitude, so the column number densities of O and N 2 at the altitude where the N 2 column number density is 1 × 10 17 /cm 2 is mainly from altitudes immediately above this level (∼140–180 km) (Yu, Ren, Le, et al., 2020; Yu, Ren, Yu, et al., 2020). This altitude region encompasses most of LBH radiance and minimizing the uncertainty in ∑O/N 2 as a function of 135.6 nm/LBH.…”
Section: Introductionmentioning
confidence: 99%
“…Based on GUVI limb measurements, Yu et al. (2020) suggested that [O]/[N2] $[O]/[{N}_{2}]$ volume density ratio presents prominent annual and semiannual variations with solar activity dependence. The upwelling of the oxygen‐depleted or nitrogen‐rich air from much lower altitude in the thermosphere into the F‐region during the geomagnetic storm is reported in previous studies (e.g., Buonsanto, 1999; Mayr & Volland, 1972; Prölss, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…𝑁𝑁2] is affected by the horizontal and vertical motion of neutral particles, molecular diffusion, and other effects in the thermosphere, which are relevant to the solar activity and geomagnetic disturbance. Based on GUVI limb measurements, Yu et al (2020) 𝑁𝑁2] volume density ratio presents prominent annual and semiannual variations with solar activity dependence. The upwelling of the oxygen-depleted or nitrogen-rich air from much lower altitude in the thermosphere into the F-region during the geomagnetic storm is reported in previous studies (e.g., Buonsanto, 1999;Mayr & Volland, 1972;Prölss, 1980).…”
Section: The Ratio Of 𝐴𝐴mentioning
confidence: 99%